The impact of the QR code content and customer experience on QR code usage intention and customer satisfaction : an analysis in the context of food packaging - Sousa, Eva de Sá Santos (2021)
Since 1994, companies have been using Quick Response (QR) codes. Nevertheless, their acceptance is considerably recent due to the increase of smartphone usage and the integration of QR code scanner applications on smartphones. As a result, QR codes became available in the most diverse locations, including food packaging, which is the focus of this study. Smart packaging creates interactive communications between the product and the customers based on the content, which varies from information to entertainment. Previous studies validated that effective QR code campaigns impact customers’ experience and generate higher customer satisfaction levels. In the current study, the author hypothesizes that the type of content made available in the QR code influences the customer experience. Entertaining content impacts the sensory, affective, behavioral, and social dimensions more than informative content. Meantime, informative content affects significantly more the intellectual dimension. Besides, the author investigates the effect of the customer experience on the QR code customer satisfaction and the QR code usage intention. Results reveal that entertaining content has a more positive influence on the behavioral dimension of customers’ experience than informative content. For the remaining customer experience dimensions, the types of content behave similarly. Moreover, all the customer experience dimensions, except the affective, positively impact the QR code customer satisfaction and the QR code usage intention. The QR code customer satisfaction partially mediates the relationship between the customer experience dimensions and the QR code usage intention. Lastly, the study presents its implications, limitations, and suggestions for future studies.